2000
DOI: 10.1006/dbio.2000.9839
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Fgf4 Gene Expression in the Myotomes Is Regulated by Myogenic bHLH Factors and by Sonic Hedgehog

Abstract: The Fgf4 gene encodes an important signaling molecule which is expressed in specific developmental stages, including the inner cell mass of the blastocyst, the myotomes, and the limb bud apical ectodermal ridge (AER). Using a transgenic approach, we previously identified overlapping but distinct enhancer elements in the Fgf4 3' untranslated region necessary and sufficient for myotome and AER expression. Here we have investigated the hypothesis that Fgf4 is a target of myogenic bHLH factors. We show by mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…1C, blue and purple arrows). It has been previously shown that Myf5 and Myod1 are required for FGF expression in the mouse myotome (Fraidenraich et al, 2000;Grass et al, 1996), and that FGF signaling is essential for Scx induction in chick (Brent et al, 2003). Building on these findings, we decided to compare expression of Scx and the myotomal FGFs in mouse.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…1C, blue and purple arrows). It has been previously shown that Myf5 and Myod1 are required for FGF expression in the mouse myotome (Fraidenraich et al, 2000;Grass et al, 1996), and that FGF signaling is essential for Scx induction in chick (Brent et al, 2003). Building on these findings, we decided to compare expression of Scx and the myotomal FGFs in mouse.…”
Section: Resultsmentioning
confidence: 93%
“…Interestingly, it appears that the events of specification of the somitic muscle progenitors and onset of myotomal FGF signaling are closely linked: in Myf5 -/-mutants, expression of the myotomal FGFs is delayed until induction of Myod1, and in Myf5 -/-; Myod1 -/-double mutants, expression is never initiated (Fraidenraich et al, 2000;Fraidenraich et al, 1998;Grass et al, 1996). Moreover, the dependency of FGF expression on induction of Myf5 and Myod1 appears to be direct.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, expression of Pea3, Erm, and Scx in the anterior and posterior sclerotome and dermomyotome appears to be a response to myotomal expression of Fgf8: while Fgf8 is expressed throughout somite development, Pea3, Erm and Scx only become restricted to their respective sclerotomal and dermomyotomal domains after Fgf8 has become localized in the myotome. In mouse, it has been shown that expression of FGFs in the myotome is directly controlled by a myotomespecific enhancer activated by the myogenic determinancy factors Myf5 and Myod; thus, it is only upon differentiation that the myofibers express FGFs (Fraidenraich et al, 2000;Grass et al, 1996). Additionally, there is evidence in both mouse and chick that sonic hedgehog signaling arising from the ventral midline is required for expression of the myotomal FGFs (Fraidenraich et al, 2000;Huang et al, 2003).…”
Section: Myotomal Fgf Signaling Regulates Gene Expression In the Syndmentioning
confidence: 99%
“…In mouse, it has been shown that expression of FGFs in the myotome is directly controlled by a myotomespecific enhancer activated by the myogenic determinancy factors Myf5 and Myod; thus, it is only upon differentiation that the myofibers express FGFs (Fraidenraich et al, 2000;Grass et al, 1996). Additionally, there is evidence in both mouse and chick that sonic hedgehog signaling arising from the ventral midline is required for expression of the myotomal FGFs (Fraidenraich et al, 2000;Huang et al, 2003).…”
Section: Myotomal Fgf Signaling Regulates Gene Expression In the Syndmentioning
confidence: 99%